2015
DOI: 10.1002/job.2075
|View full text |Cite
|
Sign up to set email alerts
|

Juggling work and family responsibilities when involuntarily working more from home: A multiwave study of financial sales professionals

Abstract: Using multiwave survey data collected among 251 financial sales professionals, we tested whether involuntarily working more from home (teleworking) was related to higher time-based and strain-based work-tofamily conflict (WFC). Employees' boundary management strategy (integration vs. segmentation) and work-family balance self-efficacy were considered as moderators of these relationships. Data were collected one month before, three months after, and 12 months after the implementation of a new cost-saving policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
130
2
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(168 citation statements)
references
References 56 publications
6
130
2
6
Order By: Relevance
“…But what if it is not voluntary? Lapierre et al () show that non‐voluntary working from home is associated with negative outcomes such as strain resulting from work–family conflict. It would be valuable to conduct research that takes into account the fact that some employees work voluntarily from home while others do not, and the effect this distinction has on performance.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…But what if it is not voluntary? Lapierre et al () show that non‐voluntary working from home is associated with negative outcomes such as strain resulting from work–family conflict. It would be valuable to conduct research that takes into account the fact that some employees work voluntarily from home while others do not, and the effect this distinction has on performance.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…These elements of the gloomy perspective can reduce work performance, hinder recovery, detract from WLB, and create work-family conflict. In fact, among the 37 studies reviewed here, study samples include those from Finland (Kinnunen et al, 2017), Belgium (Schooreel & Verbruggen, 2016), El Salvador (Las Heras, Rofcanin, Bal, & Stollberger, 2017, and the Netherlands (Biron & Van Veldhoven, 2016;Derks et al, 2015;LaPierre, Steenbergen, Peeters, & Kluwer, 2016;ten Brummelhuis & Van der Lippe, 2010). This suggests that this is not only the fastest growing stream of research but also perhaps the most diverse and generalizable mechanism of work-family backlash in terms of cross-cultural implications.…”
Section: Mechanism 3: Spillovermentioning
confidence: 92%
“…Macro. Organizations are innovating FWAs by restricting employee control-including involuntary work from home policies-as a means to save on overhead and reduce the size of physical office spaces (Lapierre et al, 2016). Yet, these policies are often mistakenly categorized or intentionally disguised as WLB policies (Fleetwood, 2007).…”
Section: Future Research Agendamentioning
confidence: 99%
“…For example, a study of 251 sales professionals found that involuntary telework led to higher levels of strain-based work-to-family conflict and, among those who indicated low self-efficacy for managing the multiple demands of the home and work environment, there was an increase in both time and strain-based work-to-family conflict (Lapierre et al, 2016). This suggests that attitudes toward telework are unlikely to be positive if telework has been imposed on rather than chosen by employees, and negative attitudes are more likely to produce negative outcomes.…”
Section: Implications For Theory and Practicementioning
confidence: 99%